Behind closed doors : domestic violence in India - Bhattacharya, Rinki (SAGE Publications, 2004)
This powerful book deals with the complex problem of domestic violence in India. Based on the narratives of 17 women from diverse socioeconomic and caste backgrounds, the author locates the problem in the larger societal context and analyzes a range of physical, psychological, non-physical, social and cultural aspects of the abuse of women.